Dollarization, Monetary Policy, and the Pass-Through - Ize, Alain; Parrado, Eric. (Washington, D.C. : International Monetary Fund, 2002)
This paper explores how real dollarization (dollar indexing of wages), financial dollarization (dollar denomination of financial contracts), and monetary policy interact in a general equilibrium, new open-economy macroeconomics model with real shocks. Real dollarization is avoided as long as the home monetary authorities conduct monetary policy optimally (maximize local welfare). Suboptimal monetary policies are more likely to induce real dollarization when the correlation between domestic and external shocks is high, since in this case the (presumably optimal) foreign monetary policy guarantees a better level of protection against macroeconomic uncertainty. While real dollarization contributes to financial dollarization, important asymmetries between the two were found.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet